RESPONSE OF COCONUT AND COFFEE TO FERTILIZERS APPLIED ON EITHER OR BOTH CROPS IN AN INTERCROPPING SYSTEM - R.Z. Margate; J.N. Maravilla; R.M. Ebuna; M.N. Eroy (International Coconut Community, 1994)
A study to assess the effects of fertilizer application on either coconut or coffee or both, in an intercropping system was conducted from 1985 to 1991. at the Davao Research Center, Mindanao, Philippines. The coconuts were planted at 8 m x 8 m square system. Fertilizer application on coconut intercropped with either fertilized or unfertilized coffee increased copra yield significantly. A very slight increase in copra per nut was noted on un‑fertilized coconut even with fertilized coffee intercrop indicating coconut did not benefit from the fertilizers applied on coffee. Bean yield of fertilized coffee was increased significantly by 202 percent under fertilized or unfertilized coconuts. But yield of unfertilized coffee did not increase even under fertilized coconut. There is a need to apply fertilizers separately to both crops. Economic analysis revealed that fertilizer application to both coconut and coffee gave the highest net return, followed by fertilizer application on coffee alone.